Complex Hydrides for Energy Storage, Conversion, and Utilization. Issue 50 (4th November 2019) - He, Teng; Cao, Hujun; Chen, Ping
Abstract: Functional materials are the key enabling factor in the development of clean energy technologies. Materials of particular interest, which are reviewed herein, are a class of hydrogenous compound having the general formula of M(XH n ) m, where M is usually a metal cation and X can be Al, B, C, N, O, transition metal (TM), or a mixture of them, which sets up an iono‐covalent or covalent bonding with H. M(XH n ) m is generally termed as a complex hydride by the hydrogen storage community. The rich chemistry between H and B/C/N/O/Al/TM allows complex hydrides of diverse composition and electronic configuration, and thus tunable physical and chemical properties, for applications in hydrogen storage, thermal energy storage, ion conduction in electrochemical devices, and catalysis in fuel processing. The recent progress is reviewed here and strategic approaches for the design and optimization of complex hydrides for the abovementioned applications are highlighted. Abstract : The rich chemistry between H and B/C/N/O/Al/transition metal (TM) allows complex hydrides of diverse composition and electronic configuration, and thus tunable physical and chemical properties, with applications in hydrogen storage, thermal energy storage, ion conduction, and catalysis. The recent progress is reviewed and the strategic approaches for the design and optimization of complex hydrides for the abovementioned applications are highlighted.